SEA0400, a novel Na+/Ca2+ exchanger inhibitor, reduces calcium overload induced by ischemia and reperfusion in mouse ventricular myocytes - Wang, J; Zhang, Z; Hu, Y; Hou, X; Cui, Q; Zang, Y; Wang, C (Physiological research, 2007)
Given the potential clinical benefit of inhibiting Na+/Ca2+ exchanger (NCX) activity during myocardial ischemia reperfusion (I/R), pharmacological approaches have been pursued to both inhibit and clarify the importance of this exchanger. SEA0400 was reported to have a potent NCX selectivity. Thus, we examined the effect of SEA0400 on NCX currents and I/R induced intracellular Ca2+ overload in mouse ventricular myocytes using patch clamp techniques and fluorescence measurements. Ischemia significantly inhibited inward and outward NCX current (from -0.04±0.01nA to 0 nA at -100 mV; from 0.23±0.08 nA to 0.11±0.03 nA at +50 mV, n=7), Subsequent reperfusion not only restored the current rapidly but enhanced the current amplitude obviously, especially the outward currents (from 0.23±0.08 nA to 0.49±0.12 nA at +50 mV, n=7). [Ca2+]i, expressed as the ratio of Fura-2 fluorescence intensity, increased to 138±7 % (P<0.01) during ischemia and to 210±11 % (P<0.01) after reperfusion. The change of NCX current and the increase of [Ca2+]i during I/R can be blocked by SEA0400 in a dose-dependent manner with an EC50 value of 31 nM and 28 nM for the inward and outward NCX current, respectively. The results suggested that SEA0400 is a potent NCX inhibitor, which can protect mouse cardiac myocytes from Ca2+ overload during I/R injuries.
Keywords: Aniline Compounds; aniliny; Myocardial Reperfusion; pumpa pro výměnu sodíku a vápníku; Financing, Government; metoda terčíkového zámku; financování vládou; Mice, Inbred C57BL; fenylethery; myši inbrední C57BL; Sodium-Calcium Exchanger; ischemická choroba srdeční; Phenyl Ethers; Myocardial Ischemia; Patch-Clamp Techniques; Myocytes, Cardiac; reperfuze myokardu; kardiomyocyty